KATA KERJA BANTU MODAL DALAM DRAMA A DOLLâ€™S HOUSE KARYA HENRIK IBSEN - Tumbelaka, Riani Meigi (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT There are two subclasses of verbs in English: those are lexical verb and auxiliary verb. Three types of auxiliary verbs are: tense auxiliaries, do auxiliary, and modal auxiliaries. Modals are a class of auxiliary verbs that combine with the base form to make verb phrase with a wide meaning. Â This study is an attempt to describe and analyze modals in the drama â€œA Dollâ€™s Houseâ€ by Henrik Ibsen. The aim of this research is to identify and classify the form and meaning of modals. Â The method which is used in this research is descriptive method. The data of modals have been taken from the sentences in the drama â€œA Dollâ€™s Houseâ€ and have been analyzed by using Azarâ€™s concept. Â The result of this study shows that modal forms which are used namely can, may, must, will, should, could, might, and would. Ought to, had better, and shall are not found in the drama â€œA Dollâ€™s Houseâ€. Â The study can be continually done by analyzing modals in other literary works by using the concept of Azar. Keywords : Modals, English, Drama A Dollâ€™s House